2007
DOI: 10.1002/nla.526
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of block matrix preconditioners for elliptic optimal control problems

Abstract: SUMMARYIn this paper, we describe and analyse several block matrix iterative algorithms for solving a saddle point linear system arising from the discretization of a linear-quadratic elliptic control problem with Neumann boundary conditions. To ensure that the problem is well posed, a regularization term with a parameter is included. The first algorithm reduces the saddle point system to a symmetric positive definite Schur complement system for the control variable and employs conjugate gradient (CG) accelerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…Solution algorithms for variants of the system (28) have been studied by various authors, cf. for example (Nielsen and Mardal, submitted) 42–44. The discussion here follows closely the approach taken in 44.…”
Section: Parameter‐dependent Problemsmentioning
confidence: 92%
See 1 more Smart Citation
“…Solution algorithms for variants of the system (28) have been studied by various authors, cf. for example (Nielsen and Mardal, submitted) 42–44. The discussion here follows closely the approach taken in 44.…”
Section: Parameter‐dependent Problemsmentioning
confidence: 92%
“…Algorithms for other optimal control problems with elliptic PDE constraints are discussed in, e.g. Nielsen and Mardal (submitted) 42–44.…”
Section: Preconditioning Discrete Saddle Point Problemsmentioning
confidence: 99%
“…that the number of iterations needed does not increase significantly as α → 0. The latter type of problem has been addressed in many papers for various models [1,7,22,27,31,32,34,35,37] -i.e. for special cases of elliptic and parabolic control problems.…”
Section: Introductionmentioning
confidence: 99%
“…Of course also multigrid methods have been considered for optimal control problems, see, e.g., [10]. A review of block approaches to optimal control problems can be found in [9]. A recent block approach can be found in [11].…”
Section: Introductionmentioning
confidence: 99%